Evaluation of the treatment results of laryngeal carcinoma: our experience over 10 years - (:unkn) unknown (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2012)
Aim: To retrospectively analyze the treatment results for laryngeal carcinoma and to find the impact of the clinical parameters on the survival of the patients. Materials and methods: The medical records of 150 consecutive patients, operated on for laryngeal squamous cell carcinoma between 1991 and 2009, were reviewed. Tumor localization, TNM stages, treatment modalities, radiotherapy, second primary tumors, and tumor recurrence were recorded, and the survival data were obtained. Results: Neck metastasis was rare (3.6%) in T1 and T2 glottic tumors, while there was a significant increase in the rate of N+ neck (35%) in T3 and T4 glottic tumors (P < 0.05). N+ neck was encountered in 28% of the early and 33% of the late-stage supraglottic cancers (P > 0.05). There was a significant relation between survival and tumor recurrence (P < 0.05), whereas the other clinical parameters were not associated with survival (P > 0.05). The risk for death of the disease increased by 63.3% when tumor recurrence occurred (odds ratio = 6.3573). Conclusion: Aggressive treatment of the primary tumor and neck may eliminate the impact of advanced tumor stage on survival. Local and regional recurrence and second primary diagnosis are the most important factors involved in survival in laryngeal carcinoma.
Keywords: Laryngeal carcinoma; treatment; prognosis; recurrence; survival; SQUAMOUS-CELL CARCINOMA; NECK DISSECTION; PROGNOSTIC-FACTORS; GLOTTIC CARCINOMA; T3 N0; CANCER; RADIOTHERAPY; RECURRENCE; CHEMORADIOTHERAPY; METASTASIS